The Dual-Center Global Financial System The Perspective of China's Rise - YUAN, Tao (Springer Singapore, 2018)
This book focuses on the systematic change in the global economy accompanying the rise of China. Once China has the same huge and advanced economy as the U.S., the global economy's current one-center system will have a chance to change: China will represent an alternative center. If it can satisfy essential criteria for the global economy such as a stable foreign exchange system, healthy international trade environment and strong support for economic development etc., China will be able to offer a viable alternative. In this constellation the two centers of the global economy and financial system, the U.S. and China, would ideally cooperate, and the global economy could benefit from having two economic and financial centers.